Leśmian: Ja i Inny - Czabanowska-Wróbel, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
Leśmian’s poems, those that can be treated as parables with the thirdperson narrator and a given plot and those written with the lyrical I and straightforward narrative, include a dominant and premeditated anthropological conception. Leśmian is intrigued by the relation between an individual and other people. The relation is conducive, or even essential, in the spiritual survival of the individual, and is often described as a “salvation”. The relevant issues can be interpreted within the language of the philosophy of dialogue, including the philosophy of Emmanuel Lévinas, though the latter cannot be obviously treated in terms of decisive influence. The space where the ethical dimension of the interpersonal relations is revealed is namely love towards the closest pesons, it is followed by the encounter with other people, and finally the encounter with radical otherness, with what is, beyond the very experience of humanity, different — with a suffering animal. In Leśmian’s poetical output, in which the ontological and epistemological dimensions are so important, it is rather the ethical dimension that becomes prominent. This dimension, often neglected by researches of the poet’s rich and versified output, quite unexpectedly seems to come down to some absolutely fundamental ethical imperatives: to love and keep in mind that one should not hurt or kill with words or deeds.